Analisis Hubungan Eksekutif dan Legislatif dalam Pembuatan Peraturan Daerah di Kota Palopo - Perkasa, Adithia Anbar; Yunus, Rabina; Rusli, Andi Muhammad (Program Studi Ilmu Pemerintahan Fisip Unhas, 2013)
Abstract: This study analyzing the relationship between regional executive ( a regional government ) with regional legislative ( sub-national parliaments ) in making the bylaw in the city of palopo .Data collection is done by using interview technique , the study documents , and observation .Interviews were held with the respondents who represent the council and local governments .Respondents dipiiih deliberately by taking into account progress of involvement in the process of making local regulations. The results of research showing the relation legislative and regional executive in the discussion process and determination of bylaw happened relationship that is both reciprocal (resiprokal). In the act of no. 32 / 2004 next upgrade into a law no. 23 2014 affirming that in process of making regional regulation, the council and the local government does not each other dominated, nevertheless council has not been fully capable of offset the local government especially for reasons of internal the members of the like the education and experience, the other factors that affect relations executive and legislative in making regional regulation is communication and political interests .The connection communication, cooperation and clarification, is expected to be able to create local regulations which accommodate various aspirations and public interest.Keywords: executive, legislative, resiprocal, regulationAbstrak: Penelitian ini menganalisis hubungan antara eksekutif daerah (Pemerintah Daerah) dengan legislatif daerah (Dewan Perwakilan Rakyat Daerah) dalam pembuatan peraturan daerah (perda) di Kota Palopo. Pengumpulan data dilakukan dengan menggunakan teknik wawancara, studi dokumen, dan observasi. Wawancara dilakukan terhadap responden yang mewakili DPRD dan Pemerintah Daerah.Hasil penelitian menunjukkan hubungan legislatif dan eksekutif daerah dalam proses pembahasan dan penetapan perda terjadi hubungan yang bersifat timbal balik (resiprokal). Dalam Undang-Undang Nomor 32 Tahun 2004 yang selanjutnya diperbahurui ke Undang-Undang Nomor 23 Tahun 2014 menegaskan bahwa dalam proses pembuatan peraturan daerah, DPRD dan Pemerintah daerah tidak saling mendominasi, Meskipun demikian DPRD masih belum sepenuhnya mampu mengimbangi Pemda terutama karena alasan internal anggota DPRD seperti tingkat pendidikan dan pengalaman, faktor lain yang mempengaruhi hubungan eksekutif dan legislatif dalam membuat peraturan daerah adalah komunikasi dan kepentingan politik.. Adanya hubungan komunikasi, kerjasama dan klarifikasi, diharapkan akan mampu menciptakan perda yang dapat mengakomodasi berbagai aspirasi dan kepentingan masyarakat.Kata kunci: eksekutif, legislatif, resiprokal, peraturan